Hydroponics as a tool in wheat breeding - Du Toit, Andreas Gerhardus Adriaan (University of the Free State, 2005)
The aims of this study were to evaluate the functionality and the practicality of hydroponics in the process of wheat breeding compared to a conventional glasshouse cultivation method. Furthermore for assessing the screening capability of drought tolerance in wheat cultivars using a hydroponic system was used and morphological yield components were measured and protein concentration fluctuations by means of SE-HPLC were analyzed. x In the first study, five South African wheat cultivars, SST 88, Baviaans, Steenbras, SST 876 and Kariega, were planted into two identical hydroponic systems. A second set of the five cultivars where planted two months after the first planting to separate the two stress periods, the first being drought stress before seed fill and in the second planting, stress was induced at seedling stage. This was done simultaneously. x When maturity was reached, several yield component measurements were taken. x The influences of the drought treatment on the different yield components were established. x Protein extracts of wheat flour were analyzed by SE-HPLC. x SDS was used for the first protein extraction step, and the rest of the proteins were extracted by sonication. 89 x The SE-HPLC method fractionated the storage proteins (both SDS-soluble and SDS-insoluble) into four distinct peaks of decreasing molecular size range, representing mainly larger polymeric proteins (mainly HMWglutenins), smaller polymeric proteins (mainly LMW-glutenins), larger monomeric proteins (mainly gliadins), and smaller monomeric proteins (mainly albumins and globulins). x Relationships between the amount and size-distribution of polymeric and monomeric proteins and flour quality properties were established. x The influence of the drought treatment on protein fractions and quality characteristics was also determined by SE-HPLC. x The results showed that both the genotype and drought conditions had a significant influence on the yield components and protein characteristics. x The use of a hydroponic cultivation method for the induction of drought conditions at any stage of development of wheat can be done at a highly significant level, not only for inducing stresses but for re-establishing and maintaining optimum conditions as well. x SE-HPLC provided a simple and an objective test for measuring the relative size-distributions of wheat storage proteins. x In the second study two South African wheat cultivars, Baviaans and Steenbras, were planted into two identical hydroponic systems (differing only in the makeup of the nutrient solution) and in pots. x Emergence percentages and dates were recorded for a one month period after the emergence of the first seedling in the experiment. x When maturity was reached several yield component measurements were taken. 90 x The two hydroponic systems provided a better emergence environment compared to the potting solution, indicating that there is already a higher potential number of crosses that can be made in the breeding program using a hydroponic cultivation method. x The effect of treatment was highly significant for most of the yield characteristics, indicating that the effectiveness of the treatments played a significant role in the yield potential of each cultivar. x Findings indicated that by using a hydroponic cultivation method instead of the potting method for growing wheat, parent lines can increase the amount of crosses that can potentially be made, thus increasing the amount, potential success and quality of the crosses made, together with the potential of producing seeds that will have the potential of a higher emergence rate. x The hydroponic cultivation method using the chemicult solution proved to be the most effective method of cultivation during this study.

Die doel van die studie was die evaluering van die effektiwiteit en die praktiese toepassing van ‘n hidroponiese koring kultiveringsproses teenoor die konvensionele pot-aanplantingsmetode. Die tweede doel was om die doeltreffendheid van ‘n hidroponiese stelsel vir gebruik in ‘n droogtestremmingstoets vir koring te evalueer deur die opbrengspotensiaal asook die fluktuasie van proteïene deur middel van SE-HPLC te meet. x In die eerste studie is vyf Suid-Afrikaanse lentekoringkultivars nl. SST 88, Baviaans, Steenbras, SST 876 en Kariega, in twee identiese hidroponiese stelsels geplant. ‘n Tweede stel van die vyf kultivars is twee maande later geplant in dieselfde stelsel om die stremmingsperiodes van die studies te skei. Die stremming is toegepas tydens die blomstadium van die eerste proef, en op die saailingstadium van die tweede proef. Die proewe is gelyktydig uitgevoer. Na rypwording is opbrengskomponente gemeet en vergelyk. Die invloed van die droogtestremming op die opbrengskomponente is bepaal. SE-HPLC is gebruik om proteïen-ekstrakte van die meel te ontleed. SDS is tydens die eerste ekstraksieprosedure gebruik. Die SDS-onoplosbare proteïene is daarna met behulp van sonifisering geëkstraheer. The SE-HPLC metode het die bergingsproteïene (beide SDS-oplosbare en SDS-onoplosbare) in vier duidelike fraksies verdeel volgens hul molekulêre gewig. Die vier fraksies (of pieke) het bestaan uit groter polimeriese proteïene (hoofsaaklik hoë molekulêre gewig gluteniene), kleiner polimeriese proteïene (hoofsaaklik lae molekulêre gewig gluteniene), groter monomeriese proteïene (hoofsaaklik gliadiene) en kleiner monomeriese proteïene (hoofsaaklik albumiene en globuliene). Die verwantskappe tussen die hoeveelhede en grootte-verspreiding van polimeriese en monomeriese proteïene en kwaliteitseienskappe is bepaal. Die invloed van die droogtestremming is op die proteïenfraksies en kwaliteitseienskappe vasgestel met behulp van SE-HPLC. Die resultate het getoon dat beide die genotipe en die droogtestremming gelei het tot betekenisvolle verskille in die kwaliteitseienskappe. Die gebruik van ‘n hidroponiese kultiveringsmetode in die uitvoering van ‘n droogtestudie kan ter enige tyd in die ontwikkeling van koring met groot sukses gedoen word; nie net vir die induksie van stremming nie, maar ook vir die herstel en handhawing van optimale groeitoestande. SE-HPLC was ‘n relatief eenvoudige en objektiewe metode om die grootteverspreiding van bergingsproteïene te bepaal. In die tweede studie is twee Suid-Afrikaanse lentekoringkultivars nl. Baviaans en Steenbras, in twee identiese hidroponiese stelsels, wat slegs in hul voedingstof samestelling verskil, in potte geplant. Die ontkiemingspersentasies is oor ‘n periode van een maand na die ontkieming van die eerste saailing gemeet. Na rypwording is verskillende opbrengskomponente gemeet. Albei die hidroponiese stelsels het beter ontkiemingsomgewings geskep teenoor die potte vir die koring. In ‘n teelprogram sal dit beteken dat daar in ‘n kruisingsblok potensieel meer kruisings gemaak sal kan word. Die invloed van die behandelings was hoogs betekenisvol vir die meeste van die opbrengsveranderlikes. Dit sal beteken dat die effektiwiteit van die behandelings ‘n betekenisvolle verskil in die opbrengspotensiaal van elke kultivar sal hê. Die resultate toon aan dat die gebruik van ‘n hidroponiese kultiveringsmetode vir koring, in plaas van die tradisionele pot-metode die kruisings potensiaal van ouerlyne kan verhoog. Die verhoging in die aantal kruisings, die potensiële sukses en kwaliteit van die kruisings, tesame met die verhoogde ontkiemingspotensiaal van die kruisingsgenerasie is voordelig in ‘n teelprogram. Die hidroponiese kultiveringstegniek wat gebruik gemaak het van die Chemicult voedingsmedium, is geïdentifiseer as die mees optimale sisteem tydens die studie.
Dissertation (M.Sc. (Plant Sciences))--University of the Free State,[2005]
Keywords: Wheat -- Breeding -- South Africa; Wheat -- Drought tolerance -- South Africa; Hydroponics; Yield components; Monomeric proteins; SE-HPLC; Polymeric proteins